2023
DOI: 10.3390/molecules28041912
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of New Biosurfactants/Bioemulsifiers from Pantoea alhagi and Their Antioxidant, Antimicrobial and Anti-Biofilm Potentiality Evaluations

Abstract: The present work aimed to develop rapid approach monitoring using a simple selective method based on a positive hemolysis test, oil spreading activity and emulsification index determinations. It is the first to describe production of biosurfactants (BS) by the endophytic Pantoea alhagi species. Results indicated that the new BS evidenced an E24 emulsification index of 82%. Fourier-transform infrared (FTIR) results mentioned that the described BS belong to the glycolipid family. Fatty acid profiles showed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Thus, the components produced by P. aeruginosa strain CGA-02 are valuable materials, not only in bioremediation and sustainable environment, but in pharmaceuticals, biomedicals, food and cosmetic industries. The biosurfactant produced by P. aeruginosa strain CGA-02 are most similar to that reported in another study [70] in which oleic acid was recorded as the most dominant fatty acid component in biosurfactant produced by Pantoea alhagi (76.26% abundance). Other microorganisms such as E.coli [71] and Candida [72] can biosynthesize oleic acid, but the P. aeruginosa strain CGA-02 in this study, produced biosurfactant with relatively higher abundance of oleic acid (80.8%).…”
Section: Kinetic Studies Of Heavy Metal Removal In the Presence Of Bi...supporting
confidence: 85%
“…Thus, the components produced by P. aeruginosa strain CGA-02 are valuable materials, not only in bioremediation and sustainable environment, but in pharmaceuticals, biomedicals, food and cosmetic industries. The biosurfactant produced by P. aeruginosa strain CGA-02 are most similar to that reported in another study [70] in which oleic acid was recorded as the most dominant fatty acid component in biosurfactant produced by Pantoea alhagi (76.26% abundance). Other microorganisms such as E.coli [71] and Candida [72] can biosynthesize oleic acid, but the P. aeruginosa strain CGA-02 in this study, produced biosurfactant with relatively higher abundance of oleic acid (80.8%).…”
Section: Kinetic Studies Of Heavy Metal Removal In the Presence Of Bi...supporting
confidence: 85%
“…genus representatives could produce biosurfactants with an emulsification index exceeding 70%, thereby reducing the surface tension of the nutrient medium from 72 to 31 mN m −1 [35]. Additionally, Essghaier et al (2023) demonstrated that endophytes of Pantoea alhagi species are capable of producing biosurfactants with an emulsifying activity of 82% [36]. The species representative of B. tequilensis LK5.4 exhibited a maximum emulsification index of 52% [32].…”
Section: Glycerolmentioning
confidence: 97%
“…Biosurfactants comprise a group of unique amphiphilic molecules of microbial origin that are capable of interacting with lipidic components of microorganisms, altering their physicochemical properties [ 11 ]. It has been established that several of these compounds exhibit biological properties (antimicrobial and antifungal activity) [ 40 ] that make them potentially suitable for use in medical, pharmaceutical, and agricultural applications [ 41 ].…”
Section: Antimicrobial and Antibiofilm Activity Of Biosurfactantsmentioning
confidence: 99%